Differential protein sysnthesis during the life cycle of the protozoan parasite Trypanosoma brucei - Shapiro, S.Z.; Kimmel, A.E. (Wiley, 1987)
Two‐dimensional polyacrylamide gel electrophoresis has been used to analyze changes in protein content and protein synthesis in three stages of the life cycle of the protozoan parasite Trypanosoma brucei. The stages examined were slender and stumpy mammalian bloodstream forms and procyclic forms, which are analogous to the tsetse fly midgut stage. Two‐dimensional gels of 35S‐methionine‐labeled proteins were examined by autoradiography to analyze newly synthesized protein, and gels were stained with ammoniacal silver to analyze proteins present. Several stage‐specific molecules were noted. The most obvious was the variant surface glycoprotein, which was only present in bloodstream forms. Some other proteins were also bloodstream form specific; they had molecular weights of 120,000 and 38,000. Proteins of 52,000, 46,000, 25–30,000, and 16,000 daltons were present both in stumpy forms and procyclics but not in slender‐form trypanosomes. Several proteins (molecular weights of 50–70,000, 43,000, 40,000, 26–24,000, 20–25,000, and 15,000) were present only in one of the three stages. One protein, a molecule of about 18,000 daltons present in both slender and stumpy parasites, did not appear to be synthesized in the stumpy stage. In vitro translation products of mRNA purified from the three stages were also examined. The abundance of mRNA encoding a protein of about 40,000 daltons appeared to be greater in slender than in stumpy parasites although the stumpy forms contained more of the protein and synthesized it at a higher rate.